ANALISIS KUALITAS BUTIR SOAL UJIAN SEKOLAH KELAS IX MATA PELAJARAN MATEMATIKA - Habiba Ulfahyana (Almeera Education, 2022)
The study aims to examine the quality of the items of school examination for grade IX in Mathematics Subject at SMPN 2 Unggulan Maros (a distinguished school) in academic year of 2021/2022 based on the content validity, internal criteria validity, difficulty level, discriminating power, distractor effectiveness, and reliability. The type of this study is descriptive quantitative research. The data collection technique employed documentation technique by citing the school examination result data of grade IX in Mathematics subject at SMPN 2 Unggulan Maros in academic year 2021/2022. The results of the study reveal that the content validity is valid based on the content validity measure; the validity of the internal criteria has one invalid out of 30 questions tested; the differentiating power is 40% which has very good discriminating power, 30% has good discriminatory power, 16% has poor discriminatory power, and 13% has worse discriminatory power; the level of difficulty has a disproportionate distribution of difficulty levels with a ratio of difficult: medium : easy are 7% : 30% : 63% respectively; the effectiveness of distractors generally has a functional distractor because out of 30 questions tested, there are 22 questions (73%) with effective distractor options and 8 items (27%) with ineffective distractor option; and the reliability os obtains the test reliability coefficient at 0.830 so the test instrument is confirmed as consistent.